(untitled) (MCIT: Proceedings of International scientific and practical conference, 2021)
Vessel control in a storm is the most difficult stage in the vessel voyage, as it requires quick decisions to be made in difficult conditions. Practical experience shows that the deterioration of the working conditions of the crew is usually associated with increase in the number of control mistakes [1]. The article examines the possibility of automatic control of a vessel in a stormy conditions by automatic calculation in the on-board controller of the vessel optimal safe speed and course during a storm. This allowed to significantly increase the accuracy of calculations, to exclude the human factor, to reduce the depletion of the crew, to increase the reliability of the vessel control in a storm. The efficiency and effectiveness of the method, algorithmic and software were tested on Imitation Modeling Stand in a closed loop with mathematical vessel models of the navigation simulator Navi Trainer 5000.